2017
DOI: 10.1002/stc.2088
|View full text |Cite
|
Sign up to set email alerts
|

Partial mass isolation system for seismic vibration control of buildings

Abstract: Summary In a previous study, the authors studied a partial mass isolation (PMI) system that through isolating different portions of story masses can provide a building with multiple inherent vibration suppressors. It was shown that the PMI strategy with isolated mass ratios (IMRs) of 0.05 or 0.90 could perform as effectively as an equivalent tuned mass damper or a base isolation system, respectively. In the present paper, the PMI system is examined in structural models with different fundamental periods. PMI c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…In previous works, the authors studied MFI configurations with different isolated mass ratios (IMRs) in 6-, 12-, 20-, and 40-story buildings. [20,21] A deterministic design optimization was conducted through minimizing interstory drift responses of the structural frame under stochastic excitations. It was shown that an MFI system with a low IMR (e.g., 5%) provides sufficient inherent mass to negate the need to add an external mass damper to the system; at a high IMR (e.g., 90%), an MFI system exhibits a global dynamic response reduction similar to the one obtained using a traditional BI system.…”
Section: Robustness Of Common Passive Control Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous works, the authors studied MFI configurations with different isolated mass ratios (IMRs) in 6-, 12-, 20-, and 40-story buildings. [20,21] A deterministic design optimization was conducted through minimizing interstory drift responses of the structural frame under stochastic excitations. It was shown that an MFI system with a low IMR (e.g., 5%) provides sufficient inherent mass to negate the need to add an external mass damper to the system; at a high IMR (e.g., 90%), an MFI system exhibits a global dynamic response reduction similar to the one obtained using a traditional BI system.…”
Section: Robustness Of Common Passive Control Systemsmentioning
confidence: 99%
“…It was shown that an MFI system with a low IMR (e.g., 5%) provides sufficient inherent mass to negate the need to add an external mass damper to the system; at a high IMR (e.g., 90%), an MFI system exhibits a global dynamic response reduction similar to the one obtained using a traditional BI system. Taking into account different performance objectives that deal with the mitigation of structural interstory drift, displacement and acceleration responses of isolated floor subsystems (IFSs), and structural and architectural constraints, Anajafi and Medina [20] showed that applying intermediate IMRs (e.g., 25-50%) can provide an effective and efficient MFI system.…”
Section: Robustness Of Common Passive Control Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…en, the nontraditional large mass ratio (>0.15) TMD is formed, such as the structure local isolation [6], the megasubstructure configuration [14,15], and the interlayer isolation structure system [16,17]. e noncritical components in the structure, such as filled walls and floors, can also be used as the mass blocks to form a large mass ratio TMD [18,19]. In addition, the heavy equipment in an industrial plant can be constructed into a large mass ratio TMD in the form of suspension or isolation [20].…”
Section: Introductionmentioning
confidence: 99%